Achievements in Mine Water Management and Research General Report (The Australasian Institute of Mining and Metallurgy, 1988)
Seven papers included in Session 8 of the Third International Mine Water Congress under the heading "Achievements in Mine Water Management & Research" have been reviewed. Only one paper, a case study by Masters on biological treatment of inorganically polluted effluent, has any connection with research in the sense of seeking new, generally applicable knowledge which would advance the frontiers of mine water management. The remainder deal with various aspects of the management of mine water ranging from investigation of the geology of a specific aquifer system through operating dewatering systems to the management of specific effluent disposal problems.